Improving the Cycle-life of Naphthoquinone-based Active Materials by Their Polymerization for Rechargeable Organic Batteries. (June 2016) - Yao, Masaru; Numoto, Tatsuhiro; Ando, Hisanori; Kondo, Ryota; Takeshita, Hiroyuki T.; Kiyobayashi, Tetsu
Abstract: To increase the cycle-stability of rechargeable batteries using an organic positive-electrode material, we synthesized a polymer from a 5, 8-dihydroxy-1, 4-naphthoquinone (DHNQ) skeleton, which potentially undergoes a four-electron transfer redox reaction. The polymeric material (PDHNQ) was synthesized by the condensation reaction between DHNQ and formaldehyde under acidic media conditions. The initial capacity of the electrode using the monomer (DHNQ), 193 mAh/g, quickly decayed to 56 mAh/g after 100 cycles. On the other hand, the electrode incorporating the prepared PDHNQ showed the higher initial discharge capacity of 256 mAh/g and a longer cycle-life, retaining about 133 mAh/g after 100 cycles.